2008
DOI: 10.1016/j.ejcts.2008.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for reoperation after relief of congenital subaortic stenosis☆

Abstract: Surgical relief of congenital subaortic stenosis, even with complex defects, yields excellent results. Reoperation is not infrequent, and should be anticipated with younger age at operation, complex defects, residual postoperative gradient, and an arteria lusoria. Myectomy concomitant to membrane resection, even in simple lesions, does not provide enhanced freedom from reoperation, and should be tailored to anatomic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 21 publications
8
49
1
14
Order By: Relevance
“…12 Although some previous studies have suggested that additional myectomy during the first operation reduces the incidence of recurrence, other authors have questioned this finding. 8,[16][17][18][19][20][21][22][23][24][25][26][27] Our results do not support the benefit of additional myectomy for either the risk of reoperation or LVOT gradient progression rate postoperatively. A tradeoff when aggressive surgical resection is performed to potentially lower the recurrence rate is the risk of a complete atrioventricular block, which was significantly higher in the patients who underwent additional myectomy compared with those who underwent isolated enucleation (8% versus 2%).…”
Section: Isolated Enucleation Versus Additional Myectomycontrasting
confidence: 54%
See 1 more Smart Citation
“…12 Although some previous studies have suggested that additional myectomy during the first operation reduces the incidence of recurrence, other authors have questioned this finding. 8,[16][17][18][19][20][21][22][23][24][25][26][27] Our results do not support the benefit of additional myectomy for either the risk of reoperation or LVOT gradient progression rate postoperatively. A tradeoff when aggressive surgical resection is performed to potentially lower the recurrence rate is the risk of a complete atrioventricular block, which was significantly higher in the patients who underwent additional myectomy compared with those who underwent isolated enucleation (8% versus 2%).…”
Section: Isolated Enucleation Versus Additional Myectomycontrasting
confidence: 54%
“…This has previously been demonstrated in several previous studies. 12,15,20,22,26,37 Furthermore, as expected, LVOT gradient progression postoperatively is a strong predictor for reoperation. In addition to the echocardiographic parameters to monitor and predict LVOT gradient progression, perhaps biomarkers might be useful for identifying those with more rapidly progressing disease.…”
Section: Dss Recurrence and Reoperationsmentioning
confidence: 93%
“…Развитие субаортальной обструкции, требующей по-вторной хирургической коррекции, может возникнуть как после первичных операций на сердце пo поводу изо-лированной обструкции ВОЛЖ, так и после предшеству-ющей коррекции ВПС [4,6,8,14]. Хотя субаортальный стеноз относится к категории ВПС, данный порок редко обнаруживается у новорожденных; отмечена высокая ча-стота послеоперационных рецидивов, что свидетельству-ет в пользу приобретенного происхождения патологии.…”
Section: Discussionunclassified
“…Наши данные, а также данные литературы [2,4,6,8] подтверждают возможность развития САО в любые сроки после радикальной коррекции некоторых врожденных пороков сердца, а также возникновения рецидивов после устранения САО.…”
Section: Discussionunclassified
See 1 more Smart Citation